2009
DOI: 10.1111/j.1439-0272.1991.tb02595.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of men following inguinal hernia repair

Abstract: Among 8500 patients attending the fertility clinic due to infertility, 565 men (6.65%) reported an incidence of inguinal hernioplasty with or without subsequent atrophy of the testis. Semen quality (sperm concentrations, motility, and morphology) of these patients was markedly reduced in comparison to that of fertile men. In cases where hernioplasty was followed by atrophy of the testis, damage to sperm characteristics and Sertoli cell function was found to be far greater. This was also reflected in significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 8 publications
0
14
1
Order By: Relevance
“…This is a much higher value than those reported previously, which were in the order of 0-2% 18. Incidentally, the authors of this previous study also observed high values of follicle stimulating hormone (FSH) and proposed that testicular damage may represent the result of ischemic orchitis or immunological reactions 18…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This is a much higher value than those reported previously, which were in the order of 0-2% 18. Incidentally, the authors of this previous study also observed high values of follicle stimulating hormone (FSH) and proposed that testicular damage may represent the result of ischemic orchitis or immunological reactions 18…”
Section: Discussioncontrasting
confidence: 52%
“…These findings contradict with the high proportion of infertile males who had undergone inguinal hernia surgery earlier in their lives. Although other publications report the negative effects of inguinal hernia surgery upon male patients, these usually involve inguinal hernia surgeries carried out during adulthood 18. We recommend that the long-term effects of childhood inguinal hernia surgery upon fertility should be evaluated separately.…”
Section: Discussionmentioning
confidence: 98%
“…It is the only tubular organ of the body in which the diameter of the lumen is less than the thickness of the wall. As the ductus deferens is a quite sensitive structure, especially in juveniles [10], the effect of hernia meshes on it was addressed by several authors, both in humans [6,7,11,12] and in animal models (canine [13,14]; porcine and rabbit [15,16]; rat [5,[17][18][19][20]). …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of inguinal hernia in infertile Israeli men has been reported to be 6.65% 21. Patients with a varicocele may complain of a dull throbbing scrotal pain or pulling or dragging sensation that is worsened with straining and exercise;22 however, this scrotal pain may be due to inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%